Analysis across diverse fish species highlights no conserved transcriptome signature for proactive behaviour - Rey, Sonia; Jin, Xingkun; Damsgård, Børge; Bégout, Marie-Laure; MacKenzie, Simon (BMC Genomics, 2021)
Background: Consistent individual differences in behaviour, known as animal personalities, have been demonstrated within and across species. In fish, studies applying an animal personality approach have been used to resolve variation in physiological and molecular data suggesting a linkage, genotype-phenotype, between behaviour and transcriptome regulation. In this study, using three fish species (zebrafish; Danio rerio, Atlantic salmon; Salmo salar and European sea bass; Dicentrarchus labrax), we firstly address whether personality-specific mRNA transcript abundances are transferrable across distantly-related fish species and secondly whether a proactive transcriptome signature is conserved across all three species. Results: Previous zebrafish transcriptome data was used as a foundation to produce a curated list of mRNA transcripts related to animal personality across all three species. mRNA transcript copy numbers for selected gene targets show that differential mRNA transcript abundance in the brain appears to be partially conserved across species relative to personality type. Secondly, we performed RNA-Seq using whole brains from S. salar and D. labrax scoring positively for both behavioural and molecular assays for proactive behaviour. We further enriched this dataset by incorporating a zebrafish brain transcriptome dataset specific to the proactive phenotype. Our results indicate that cross-species molecular signatures related to proactive behaviour are functionally conserved where shared functional pathways suggest that evolutionary convergence may be more important than individual mRNAs. Conclusions: Our data supports the proposition that highly polygenic clusters of genes, with small additive effects, likely support the underpinning molecular variation related to the animal personalities in the fish used in this study. The polygenic nature of the proactive brain transcriptome across all three species questions the existence of specific molecular signatures for proactive behaviour, at least at the ...